Analysis of Multicultural Values on Students Textbook of Pancasila and Citizenship Education of Senior High School Class X - Helzi Ramanta; Samsuri Samsuri (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: Analysis of Multicultural Values on Students Textbook of Pancasila and Citizenship Education of Senior High School Class X. Objectives: This study aims to analyze multicultural values on students textbook of Pancasila and Citizenship Education of Senior High School Class X. Methods: This research used content analysis method with a qualitative approach. Data source of this research was students textbook of Pancasila and Citizenship Education of Senior High School Class X Curriculum 2013 published by Ministry of Education and Culture. Data collection was done with careful anaysis and recording of the content of multicultural values in textbook. Checking the validity of the data besed on semantic validty was by observing the data in introduction consisted of sentences and illustrations images as well as the goal and scope of learning and reliability was interrater reliability that was by reading and reviewing to get consistent data. Findings: The contents of multicultural values contained in students textbook of Pancasila and Citizenship Education of Senior High School Class X consist of 15 multicultural values which include ethnohistory, religious differences, ethnocultural differences, tolerance, diversity, equality and rights of the wider community, eliminating discrimination, eliminating racism, universal humanity, conflict resolution, mediation, democracy, human rights, nature conservation, and environmental awareness. The integration of the values contained in Pancasila and Citizenship Education textbook of Senior High School Class X are each integrated through preliminary learning consisting of introductory sentences of learning, picture illustration, and learning objective: the core part which consists of a description of learning material, independent assignment, and group assignment, and the concluding part consists of reflection, summary, self-assessment, citizenship project, and competency test. Conclusion: Students textbook of Pancasila and Citizenship Education of Senior High School Class X contains multicultural values that are describe in each chapter in the students textbook. Keywords: multicultural values, textbook, and pancasila and citizenship education.